2015
DOI: 10.1080/21645515.2015.1016675
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from successful human vaccines: Delineating key epitopes by dissecting the capsid proteins

Abstract: Recombinant VLP-based vaccines have been successfully used against 3 diseases caused by viral infections: Hepatitis B, cervical cancer and hepatitis E. The VLP approach is attracting increasing attention in vaccine design and development for human and veterinary use. This review summarizes the clinically relevant epitopes on the VLP antigens in successful human vaccines. These virion-like epitopes, which can be delineated with molecular biology, cryo-electron microscopy and x-ray crystallographic methods, are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 160 publications
(158 reference statements)
0
35
0
Order By: Relevance
“…The use of synthetic biology for vaccine design is one of the strategies that have gained attention for addressing manufacturing and processing gaps of vaccine candidates. With the aid of synthetic biology and computational tools (Lua et al, ; Zhang et al, ), full length, or truncated proteins or small peptide epitopes have been molecularly inserted into viral structural proteins to generate a new class of bioengineered modular VLP vaccines (Lua et al, ; Zhang et al, ). Insertion of a RV 18 kDa VP8* antigen into the protrusion (P) domain of the norovirus capsid protein produced a highly immunogenic modular VLP subunit vaccine against RVs inside E. coli cells (Tan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of synthetic biology for vaccine design is one of the strategies that have gained attention for addressing manufacturing and processing gaps of vaccine candidates. With the aid of synthetic biology and computational tools (Lua et al, ; Zhang et al, ), full length, or truncated proteins or small peptide epitopes have been molecularly inserted into viral structural proteins to generate a new class of bioengineered modular VLP vaccines (Lua et al, ; Zhang et al, ). Insertion of a RV 18 kDa VP8* antigen into the protrusion (P) domain of the norovirus capsid protein produced a highly immunogenic modular VLP subunit vaccine against RVs inside E. coli cells (Tan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…These clinical studies demonstrated the safety and efficacy of influenza VLP vaccines, and provided an important rationale for developing VLP vaccine technology. Since baculovirus expressed VLPs contain live baculovirus and baculovirus DNA, the further improvement of the VLP production processes would be highly beneficial to eliminate baculovirus particle and DNA [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…They consist of the host envelope protein integrated with target antigens over its outer surface that overall mimics the authentic virus particle. VLP‐based vaccines that are already in use are developed against hepatitis b virus and human papillomavirus, while others targeting chikungunya virus, human immunodeficiency virus, and influenza virus have entered the clinical evaluation phase …”
Section: Virus‐like Particle (Vlp) ‐ the Technologymentioning
confidence: 99%